Improving English Speaking Skills Through AI-Based Voice Chatbots: A Systematic Review of Vocational Education Studies - Halimah, Adik Nur; Budianto, Aris; Hoesny, Mariana Ulfah; Cabuquin, Jomar C.; Ulfa, Saida (CV Sinergi Ilmu dan Publikasi, 2025)
Artificial intelligence offers teachers the opportunity to improve English-language skills among vocational high school students, enabling them to compete globally. This study aims to evaluate the effectiveness of AI-based voice chatbots through a systematic literature review. Following the PRISMA protocol, 16 articles were comprehensively analyzed after rigorous screening of 374 studies from the Scopus and ScienceDirect databases. The findings revealed a diverse range of platforms, with Duolingo dominating as the primary learning medium. The integration of voice chatbots has been shown to significantly improve students' oral performance, particularly in pronunciation, grammatical accuracy, coherence, and fluency. This improvement in speaking skills is driven by automated feedback based on repeated practice. AI-based chatbots have also been shown to increase motivation by enhancing Willingness to Communicate (WTC) and learning enjoyment through gamification elements and a non-judgmental interaction environment. Practically, vocational high school teachers are advised to integrate AI as a partner in authentic communication simulations. The study recommends learning designs that combine instant AI feedback with specific scenarios to create an adaptive and low-stress learning ecosystem.